The role of traditional knowledge in climate change adaptation among the Nicobarese of Central Nicobar Islands, India - T P Swarnam; A Velmurugan
A qualitative study guided by phenomenological approach was conducted during 2016-2018 to understand the experience of living amid climate change among the Nicobari tribes living in Central Nicobar Islands and their management practices evolved for adaptation over the years. The study showed that the economic prosperity and sustainability of Nicobarese basically depended on their traditional wisdom to mange land resources under their possession and farming practices as indicated by the strength (>6.0) of anecdotal network analysis which are evolved over the years, are found to be climate resilient. They have wealth of knowledge on island biodiversity particularly on pandanus, banana, tubers, roots and leafy vegetables besides coconut. Nicobarese also learnt the process and storage of surplus farm produce for longer duration under the existing climatic conditions. The anecdotal network analysis of nine climate change adaptation measures and eight climate change events showed that seasonal calendar and organic waste management were the best climate adaptation strategy known to tribes followed by community land use / holding.